Impacts of an egg complementary feeding trial on energy intake and dietary diversity in Malawi. Issue 1 (20th July 2020) - Lutter, Chessa K.; Caswell, Bess L.; Arnold, Charles D.; Iannotti, Lora L.; Maleta, Kenneth; Chipatala, Raphael; Prado, Elizabeth L.; Stewart, Christine P.
Abstract: Complementary feeding diets in low‐ and middle‐income countries are generally inadequate to meet requirements for growth and development. Food‐based interventions may prevent nutrient inadequacies provided that they do not displace other nutrient‐rich foods. We conducted a randomized controlled trial in rural Malawi in which 660 children aged 6 to 9 months were provided an egg a day for 6 months or assigned to a control group. Dietary intake of complementary foods and drinks was assessed at baseline, 3‐month midline and 6‐month endline visits using a tablet‐based multipass 24‐h recall. Up to two repeat recalls were collected at each time point in a subsample of 100 children per treatment group. At midline and endline, usual energy intake from eggs was about 30 kcal/day higher in the egg group compared with controls ( p < 0.0001). Compared with controls, children in the egg group were over nine times more likely to consume eggs at midline and endline. There was a comparable, but nonsignificant, greater total usual energy intake from complementary foods of 30 kcal/day at midline ( p = 0.128) and 36 kcal/day at endline ( p = 0.087). There also was a displacement of 7 kcal/day in legumes and nuts in children at endline ( p = 0.059). At midline and endline, more than 80% of children in the egg group consumed a minimally diverse diet compared with 53% at midline and 60% at endline in the control group. This study illustrates that mothers in the egg group fed eggs to young children on a regular basis without substantial displacement of other complementary foods.